2010
DOI: 10.1073/pnas.1002040107
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting mosquito sugar feeding to detect mosquito-borne pathogens

Abstract: Arthropod-borne viruses (arboviruses) represent a global public health problem, with dengue viruses causing millions of infections annually, while emerging arboviruses, such as West Nile, Japanese encephalitis, and chikungunya viruses have dramatically expanded their geographical ranges. Surveillance of arboviruses provides vital data regarding their prevalence and distribution that may be utilized for biosecurity measures and the implementation of disease control strategies. However, current surveillance meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
162
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(170 citation statements)
references
References 29 publications
8
162
0
Order By: Relevance
“…Our data and those of others (Hall-Mendelin et al 2010, van den Hurk et al 2007 clearly showed that infectious mosquitoes expectorate flaviviruses while sugar feeding and that WNV RNA is relatively stable on sugar wicks for over 5 d at ambient temperatures, agreeing with previous laboratory experiments (Johansen et al 2002, Turell et al 2002.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our data and those of others (Hall-Mendelin et al 2010, van den Hurk et al 2007 clearly showed that infectious mosquitoes expectorate flaviviruses while sugar feeding and that WNV RNA is relatively stable on sugar wicks for over 5 d at ambient temperatures, agreeing with previous laboratory experiments (Johansen et al 2002, Turell et al 2002.…”
Section: Discussionsupporting
confidence: 81%
“…However, our previous attempts using a variety of plants, fruits and inflorescence as well as sucrose solutions as trap attractants for Culex were generally unsuccessful, even though both males and females frequently feed on fructose (Reisen et al 1986). In the current study, the addition of the floral attractant phenyl acetaldehyde (Jhumur et al 2006(Jhumur et al , 2008 seemed to enhance the attraction of a 66% sucrose solution in desert habitats in the Coachella Valley, and we repeatedly were able to detect WNV RNA in sugar wicks exposed for a 5 d period.Our data and those of others (Hall-Mendelin et al 2010, van den Hurk et al 2007 clearly showed that infectious mosquitoes expectorate flaviviruses while sugar feeding and that WNV RNA is relatively stable on sugar wicks for over 5 d at ambient temperatures, agreeing with previous laboratory experiments (Johansen et al 2002, Turell et al 2002.Our sugar wick bait stations worked well in the Coachella Valley, but not elsewhere. A single sample was positive in Los Angeles and none were positive when exposed for a brief period during active enzootic transmission in Kern County.…”
supporting
confidence: 80%
“…Mosquitoes were collected with the human-landing collection method and updraft box traps equipped with white light attractant [4]. A total of 25 mosquito species were identified according to the taxonomic keys of Becker et al [2].…”
mentioning
confidence: 99%
“…Although FTA cards have previously been used to store other viruses, including arboviruses, their utility for storing infected mosquitoes has not been assessed. [10][11][12] Herein, we report laboratory-based experiments undertaken to evaluate the ability of FTA cards to preserve DENV, ZIKV, and Barmah Forest virus (BFV; an Australian alphavirus related to CHIKV) RNA in individual mosquitoes and in pools of uninfected mosquitoes up to 28 days after being removed from GATs.…”
mentioning
confidence: 99%
“…Nucleic acids were eluted from the cards using the method of Hall-Mendelin and others 12 with the modification of cutting out each mosquito sample, which was then cut into 2-4 strips depending on the size of the area of dried mosquito material. Viral RNA was extracted from 140-μL samples of the eluates using a Bio Robot Universal System (Qiagen, Hilden, Germany) and the QIAamp ® Virus BioRobot ® MDx Kit (Qiagen, Clifton Hill, Australia) according to the manufacturer's instructions.…”
mentioning
confidence: 99%